Bacterial communities associated with the ectoparasitic mites Varroa destructor and Tropilaelaps mercedesae of the honey bee (Apis mellifera). Issue 1 (14th November 2017) - Pakwan, Chonthicha; Kaltenpoth, Martin; Weiss, Benjamin; Chantawannakul, Panuwan; Jun, Guo; Disayathanoowat, Terd
Abstract: Varroa and Tropilaelaps mites have been reported as serious ectoparasites of the honey bee ( Apis mellifera ). In this study, bacterial communities associated with Varroa destructor and Tropilaelaps mercedesae from northern Thailand were determined, using both culture- dependent and culture-independent approaches. Adult female mites were collected from apiaries in Chiang Mai and Lampang provinces. Culturable bacteria were isolated from individual mites. On average, we observed approximately 1340 and 1140 CFU/mite in Varroa and Tropilaelaps, respectively. All isolates were assigned to the genus Enterococcus . Six samples of genomic DNA from 30–50 mites were extracted and subjected to pyrosequencing of bacterial 16S rRNA amplicons. The resulting 81 717 sequences obtained from Varroa were grouped into 429 operational taxonomic units. The most abundant bacteria in Varroa mites belonged to the family Enterobacteriaceae, especially the genera Arsenophonus, Enterobacter and Proteus . For Tropilaelaps mites, 84 075 sequences were obtained and clustered into 166 operational taxonomic units, within which the family Enterococcaceae (particularly the genus Enterococcus ) was predominant. Localization of bacteria in the mites using fluorescence in situ hybridization with two universal bacterial probes revealed that these bacteria were in the cecum of the mites. Taxon-specific Enterobacteriaceae and Arsenophonus probes also confirmed their localization in the cecum of Varroa . Abstract : The bacterial communities associated with two parasitic mites ( Varroa destructor and Tropilaelaps mercedesae ) of the honey bee ( Apis mellifera ) were significantly different.